2008
DOI: 10.1016/j.jphysparis.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal display of action words interferes with motor planning: A combined EEG and kinematic study

Abstract: Recent evidence has shown that processing action-related language and motor action share common neural representations to a point that the two processes can interfere when performed concurrently. To support the assumption that language-induced motor activity contributes to action word understanding, the present study aimed at ruling out that this activity results from mental imagery of the movements depicted by the words. For this purpose, we examined cross-talk between action word processing and an arm reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 54 publications
10
75
0
1
Order By: Relevance
“…Moreover, similar results were obtained in an MEG study in which subjects passively heard action verbs while their attention was focused on a silent video film, thereby supporting the view that the activation of somatotopically mapped motor regions is a fast and fairly automatic process (Pulvermüller et al 2005b; see also Shtyrov et al 2004;Moseley et al 2013). Additional evidence for this view comes from an ERP study by Boulenger et al (2008) which found that when verbs for arm/hand actions were presented to subjects subliminally, they not only modulated the "readiness potential" (an index of motor preparation) associated with subsequent reaching movements but also affected the kinematics of those movements. Finally, several behavioral studies bolster the idea that root-level motor aspects of verb meaning are retrieved quickly and more or less automatically (e.g., Boulenger et al 2006;Zwaan and Taylor 2006;Scorolli and Borghi 2007;Kaschak and Borreggine 2008;Nazir et al 2008;Taylor and Zwaan 2008).…”
Section: Speed and Automaticity Of Processingsupporting
confidence: 71%
“…Moreover, similar results were obtained in an MEG study in which subjects passively heard action verbs while their attention was focused on a silent video film, thereby supporting the view that the activation of somatotopically mapped motor regions is a fast and fairly automatic process (Pulvermüller et al 2005b; see also Shtyrov et al 2004;Moseley et al 2013). Additional evidence for this view comes from an ERP study by Boulenger et al (2008) which found that when verbs for arm/hand actions were presented to subjects subliminally, they not only modulated the "readiness potential" (an index of motor preparation) associated with subsequent reaching movements but also affected the kinematics of those movements. Finally, several behavioral studies bolster the idea that root-level motor aspects of verb meaning are retrieved quickly and more or less automatically (e.g., Boulenger et al 2006;Zwaan and Taylor 2006;Scorolli and Borghi 2007;Kaschak and Borreggine 2008;Nazir et al 2008;Taylor and Zwaan 2008).…”
Section: Speed and Automaticity Of Processingsupporting
confidence: 71%
“…For example, in an electrophysiological study that used sophisticated source localization techniques, found that verbs for leg/foot actions, arm/hand actions, and face/mouth actions elicited the expected topographic response patterns approximately 200 ms after stimulus presentation-a point in time that, according to Dehaene and Changeux (2011), is well before the roughly 300 ms threshold of conscious access (see also Shtyrov et al, 2004;Dalla Volta et al, 2014). Furthermore, in an electrophysiological study that involved subliminal presentation of verbs for arm/hand actions, Boulenger et al (2008b) found that the stimuli modulated the readiness potential (an index of motor preparation) associated with subsequent reaching movements, and also influenced the kinematics of those movements. In addition, several investigations have employed magnetoencephalography to demonstrate that action verbs engage body-part-congruent precentral motor areas with remarkable speed, in some cases as soon as 100 ms after the words can be uniquely identified (Shtyrov et al, 2014; see also Pulvermüller et al, 2005b;Moseley et al, 2013;Klepp et al, 2014; for a critique see Papeo & Caramazza, 2014).…”
Section: Processing Dynamicsmentioning
confidence: 99%
“…This logic also may be related to the 'what' versus 'how' visual streams proposed by Goodale and Milner (1992). Additional evidence can also be found by Boulenger et al (2008), finding that subliminal processing of action phrases interfered with motor performance. Taking this one step further, TMS has been used to activate the arm and leg regions of M1, significantly interfered with response time in a lexical decision task .…”
Section: Motor Imagery and Languagementioning
confidence: 72%